2012
DOI: 10.3329/bvet.v29i1.11889
|View full text |Cite
|
Sign up to set email alerts
|

Responses of monosex nile tilapia (Oreochromis niloticus) to intraperitoneal challenge by Streptococcus iniae after vaccination with ghosts of the bacterium

Abstract: The vaccine potential of Streptococcus iniae ghosts produced by gene E mediated lysis was investigated using tilapia (Oreochromis niloticus). Tilapia immunized with S. iniae ghosts (SIG) and formalin killed S. iniae (FKC) vaccines showed significantly higher serum agglutination titres than control fish. Fish immunized with SIG showed no significant differences with fish immunized with FKC in serum agglutination titres, but showed significantly higher bactericidal activity than fish immunized with FKC. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These data indicated that immunization with SAGs orally, subcutaneously, or intravenously efficiently produced bacterium-killing antibodies after a challenge. Recently, it has also been reported that S. iniae ghost vaccine stimulated higher serum bactericidal antibody levels than formalin-killed vaccine and protected experimental animals from a subsequent challenge with S. iniae (13). An earlier report showed that peptidoglycan induces strong bactericidal antibodies capable of eradicating the bacterial pathogen (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data indicated that immunization with SAGs orally, subcutaneously, or intravenously efficiently produced bacterium-killing antibodies after a challenge. Recently, it has also been reported that S. iniae ghost vaccine stimulated higher serum bactericidal antibody levels than formalin-killed vaccine and protected experimental animals from a subsequent challenge with S. iniae (13). An earlier report showed that peptidoglycan induces strong bactericidal antibodies capable of eradicating the bacterial pathogen (21).…”
Section: Resultsmentioning
confidence: 99%
“…Serum bactericidal activity (SBA) was determined as described previously (13,18), with some modifications. In brief, 100 l of a bacterial suspension (1 ϫ 10 6 CFU/ml) was added to 25 l of serum and incubated at room temperature for 1 h. After incubation, the mixture was spread onto selective medium and incubated at 37°C for 48 h. For the control, serum was replaced with PBS.…”
Section: Dna-free Sag Analysis By Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…An overnight culture of S. iniae in nutrient broth (NB) was harvested to approximately 10 6 CFU/ml and suspended in phosphate-buffer saline (PBS) (Rahman et al, 2017). Fish were anaesthetized to some extent by 60 mg/L solution of MS-222 (Sigma-Aldrich, USA) and 100 μl (10 6 CFU/ml) of bacterial suspension was intramuscularly injected at the dorsal side of each fish (Garcia, Müller, Freitas & Silva, 2010;Hossain et al, 2012).…”
Section: In Vivo Challenge Testmentioning
confidence: 99%
“…The incidence of drug-resistant Streptococcus spp. in culture fish and pond has frequently been reported in Bangladesh (Hossain, Ehsan, Rahman, Chowdhury & Haq, 2012). Consequently, screening of medicinal plant parts for herbal recovery has long been studied as an alternative of commercial drugs (Awad & Awaad, 2017;Ramudu & Dash, 2013).…”
mentioning
confidence: 99%